Konszignációs raktárkezelés a Borsodi Fémmegmunkáló Kft-nél - Horváth Melinda (2017)
The purpose of my dissertation is to present consignment storage and consignment ware-housing at the Borsodi Metal Working Ltd. in Szombathely. First of all, I introduce myself to the company, briefly about its development, its or-ganizational structure and its major partners. Then I present the storage and the consign-ment storage itself. I describe the role of storage and its location in production, distribu-tion and the entire logistics system, and I also mention warehousing costs, warehouse types and warehouse services. The main purpose of consignment storage is to always provide the user with the components or materials that are needed and available in that quantity. The point is that the warehouse is at the user's premises while the warehouse is owned by the supplier. So the user actually hires the warehouse that works on his site. The user always pays the purchase price for the items that have been agreed upon in the contract. In addition to the purchase price in the contract, it is also important to record how long the user has to take out the products. If you do not do so by the deadline indicat-ed, you will also be charged for unused products. After that, I will present my main purpose, that is, why the warehouse was created, the advantages and disadvantages of both the supplier and the user. The most important part of my dissertation is the process of how this is being done in practice, which I intend to present in detail through a product. I'm closing down what I've achieved with this type of warehouse, how economical for both parties, what are the ideas, how they change and what future plans will be. In ad-dition, I propose to the company how to maintain this level and to create more such types of warehouses with their present and future partners. The main purpose of consignment storage is to always provide the user with the components or materials that are needed and available in that quantity. The point is that the warehouse is at the user's premises while the warehouse is owned by the supplier. So the user actually hires the warehouse that works on his site. The user always pays the purchase price for the items that have been agreed upon in the contract.